Color continuum of the story 'The Golden Rose' by K.G. Paustovsky - T.V. Sivova (Ученые записки Казанского университета: Серия Гуманитарные науки)
A fragment of K.G. Paustovsky’s coloristic world view was reconstructed, which is of certain interest due to the importance of color in his works and in the light of anthropocentrism that prevails in modern linguistics. It was revealed that the color space of the story “The Golden Rose” (‘Zolotaya roza’), within the field model with zones based on both quantitative and qualitative features, is characterized by numerous color terms (for example, the field core includes 40 color terms). The color dominants of the story (black, white, yellow, and green) demonstrate the specificity of K.G. Paustovsky’s style with regard to color perception, as well as the primacy of national coloristic pattern over the individual one. The zonation of color terms shows K.G. Paustovsky’s space visualization, in which the transition occurs from the information component to the figurative one, as well as from color to light. The interrelation of color-light and space-time characteristics creates a unique color chronotope of the story “The Golden Rose”. Therefore, the identified features of K.G. Paustovsky’s color perception cast light upon his idiostyle. The results of the analysis confirm that the coloristic component played a key role in his linguistic world view.